Constraining Peptide Conformations with the Help of Ring-Closing Metathesis - Glas, Adrian; Grossmann, Tom N. (Synlett, 2015)
Chemical modifications are used to stabilize bioactive conformations of peptides thereby increasing their target affinity and selectivity. Such modified peptides proved particularly useful as inhibitors of protein–protein interactions. Most of these strategies aim at the stabilization of α-helices and β-sheets. The use of peptides with irregular secondary structure is hampered by a lack of appropriate stabilization approaches. Herein, we highlight a recent contribution from our group that uses ring-closing metathesis for the macrocyclization of peptides with irregular secondary structure. The peptide precursors are cyclized on solid support to provide cross-linked architectures that bind the human protein 14-3-3 thereby inhibiting its interaction with virulence factor exoenzyme S from Pseudomonas aeruginosa.
Keywords: cyclic peptides; hydrophobic cross-links; ring-closing metathesis; protein–protein interactions; Pseudomonas aeruginosa